Investigating the Effect of Dust Accumulation on the Solar Reflectivity of Coating Materials for Cool Roof Applications - Hamed H. Saber (Energies, 2021)
Cool roofs use reflective materials or coatings to reflect a portion of the incident solar radiation. This results in a lowering the surface temperature of the cool roof compared to black roofs, and thus helps reduce the cooling energy loads during the summer season. The research reported in this paper was conducted to assess experimentally and numerically the performance of cool and black roofs that were subjected to the hot, humid and dusty climate of Jubail Industrial City (JIC). This paper focused on characterizing one of the important properties of reflective coating material (RCM), which is its solar reflectivity. In this study, the effect of dust/dirt accumulation on the solar reflectivity of the RCM was investigated at different exposure times to the natural weathering conditions of JIC. The test results showed that dust and dirt can significantly contribute in reducing the solar reflectivity of the RCM. As such, a number of cleaning processes were conducted on the surface of the RCM so as to increase its solar reflectivity. The effect of each cleaning process on the solar reflectivity of the RCM was investigated. Finally, this paper provides a test protocol and procedure for characterizing the dust concentration/intensity on the surfaces of the RCM and cleaning this material after different exposure times to a natural and polluted climate.